PERAN SPBE (SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK) DALAM MENINGKATKAN PELAYANAN PERKARA DI PENGADILAN AGAMA MOJOKERTO - Rivaldy Lisyardo Putera; Dzulfikar Rodafi; Moh. Muslim (Jurnal Hikmatina, 2021)
To achieve clean, effective governance, transparent, & accountable quality public services & trustworthy is expected to be an electronic based government system. For increase the cohesiveness & efficiency of the based government system electronic is expected governance & governance system management nationally based electronics. The legal basis for this Presidential Decree is: Article 4 paragraph (1) of the 1945 Constitution. This Perpres regulates about: governance-based system governance electronic; electronic-based management system of government; audit information and communication technology; administrators of the government system electronic based; acceleration of electronic-based government systems; as well as monitoring and evaluation of electronic-based government systems.Keywords : goverment, system, electronic.